Early-life perturbations in glucocorticoid activity impacts on the structure, function and molecular composition of the adult zebrafish (Danio rerio) heart. (15th October 2015) - Wilson, K.S.; Baily, J.; Tucker, C.S.; Matrone, G.; Vass, S.; Moran, C.; Chapman, K.E.; Mullins, J.J.; Kenyon, C.; Hadoke, P.W.F.; Denvir, M.A.
Abstract: Background: Transient early-life perturbations in glucocorticoids (GC) are linked with cardiovascular disease risk in later life. Here the impact of early life manipulations of GC on adult heart structure, function and gene expression were assessed. Methods and results: Zebrafish embryos were incubated in dexamethasone (Dex) or injected with targeted glucocorticoid receptor (GR) morpholino knockdown (GR Mo) over the first 120 h post fertilisation (hpf); surviving embryos (>90%) were maintained until adulthood under normal conditions. Cardiac function, heart histology and cardiac genes were assessed in embryonic (120 hpf) and adult (120 days post fertilisation (dpf)) hearts. GR Mo embryos (120 hpf) had smaller hearts with fewer cardiomyocytes, less mature striation pattern, reduced cardiac function and reduced levels of vmhc and igf mRNA compared with controls. GR Mo adult hearts were smaller with diminished trabecular network pattern, reduced expression of vmhc and altered echocardiographic Doppler flow compared to controls. Dex embryos had larger hearts at 120 hpf (Dex 107.2 ± 3.1 vs. controls 90.2 ± 1.1 μm, p < 0.001) with a more mature trabecular network and larger cardiomyocytes (1.62 ± 0.13 cells/μm vs control 2.18 ± 0.13 cells/μm, p < 0.05) and enhanced cardiac performance compared to controls. Adult hearts were larger (1.02 ± 0.07 μg/mg vs controls 0.63 ± 0.06 μg/mg, p = 0.0007), had increased vmhc and gr mRNA levels. Conclusion: Perturbations in GR activity during embryonic development results in short and long-term alterations in the heart. Highlights: Embryonic glucocorticoid exposure can have direct impact on cardiac development. Altered glucocorticoid activity change the developing heart structure and function. Changes in structure, function and gene expression are also observed in later life. These subtle changes in the adult heart may increase the risk of disorder or dysfunction.